Physical, chemical and ecological performance of Syncrude Canada Ltd’s Base Mine Lake - Dunmola, A; Wytrykush, C; Heisler, D (Mine Closure 2023: 16th International Conference on Mine Closure, 2023)
Base Mine Lake (BML), the first commercial demonstration of water-capped tailings technology (WCTT) in the mineable oil sands in Alberta, Canada, was commissioned in December 2012, following seventeen years of transfer of fine tailings (FT) into West-in-pit. BML’s design basis is that over time, the FT will be physically isolated due to self-weight consolidation, the lake’s water quality will improve, and the lake will ultimately achieve targeted closure outcomes. Since commissioning, the lake has been intensively monitored to track the physical, chemical, and ecological parameters of the FT and the water cap in order to demonstrate the viability of WCTT in reclaiming FT. The FT is consolidating as predicted by finite-strain consolidation theory, reflected by increasingly distinct mudline and profile density increases with time. The water chemistry of BML is improving with decreasing concentrations of many key constituents below both acute and chronic protection of aquatic life guidelines. The lake’s ecosystem is developing, with the establishment of an aquatic invertebrate community. An adaptive management approach helps steward BML towards desired short and long-term objectives. Adaptive management actions have included alum treatment to address water turbidity, and removal of bitumen mats from the FT surface. Improvements observed in the trajectory of the physical, chemical, and ecological parameters for BML are consistent with its short-term objectives. Ongoing monitoring and adaptive management of BML will continue to ensure its long-term closure objectives are met.
Keywords: base mine lake; water-capped tailings technology; oil sands; fine tailings; aquatic closure